Country Partnership Framework for Burundi for the Period FY19-FY23 - World Bank Group (World Bank, Washington, DC, 2019)
This Country Partnership Framework (CPF) builds on lessons drawn from current engagements and recognition of the operating and reputational risks of the fragile political context. The CPF is fully aligned with WBG Strategy for Africa that aims to create sustainable and inclusive growth, strengthen human capital and build resilience to fragility and climate change. The outcome is a further shift in the Bank’s engagement toward a more citizen-centered and inclusive approach, with a focus on human development outcomes especially for the most vulnerable; building economic and social resilience; and an approach adapted to a dynamic context. The CPF expects to achieve key results by 2023 across two Focus Areas: (i) Building Human Capital and Inclusion, and (ii) Strengthening Foundations for Economic and Social Resilience.